2018
DOI: 10.1212/wnl.0000000000004998
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in high-frequency oscillation rates and amplitudes in intracranial EEG

Abstract: The anatomic variation in SOZ and non-SOZ HFO rates and amplitudes suggests the need to assess interictal HFO activity relative to anatomically accurate normative standards when using HFOs for presurgical planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 40 publications
3
65
1
Order By: Relevance
“…Their generation has been related to local balance of excitation and inhibition, interneurons being a likely key player in their generation. 39 Fast Ripples Are Very Rare in Both Eloquent and Noneloquent Cortical Areas Only 5% of all channels had 1 fast ripple every 5 minutes; these channels were also located in eloquent cortex. 34,35 Regions identified with higher ripple rates correspond to cortical regions that have a higher degree of myelination.…”
Section: Selection Of Channels From Presumably Normal Brain Regionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Their generation has been related to local balance of excitation and inhibition, interneurons being a likely key player in their generation. 39 Fast Ripples Are Very Rare in Both Eloquent and Noneloquent Cortical Areas Only 5% of all channels had 1 fast ripple every 5 minutes; these channels were also located in eloquent cortex. 34,35 Regions identified with higher ripple rates correspond to cortical regions that have a higher degree of myelination.…”
Section: Selection Of Channels From Presumably Normal Brain Regionsmentioning
confidence: 96%
“…The usefulness of this approach is underlined by a paper investigating anatomic variation of HFO rates and amplitudes inside and outside the seizure-onset zone. 39 Fast Ripples Are Very Rare in Both Eloquent and Noneloquent Cortical Areas Only 5% of all channels had 1 fast ripple every 5 minutes; these channels were also located in eloquent cortex. These findings are in keeping with work done in a smaller number of patients and brain regions.…”
Section: Selection Of Channels From Presumably Normal Brain Regionsmentioning
confidence: 96%
“…These interictal HFOs can be seen in both physiologic and pathologic situations. The HFO rates also vary according the cerebral area (Guragain et al, 2018). In pathologic situations, HFO are related to the seizure onset zone in interictal periods and have been identified in a large variety of clinical scenarios (e.g.…”
Section: High Frequency Oscillationsmentioning
confidence: 99%
“…Recent studies have shown that high frequency oscillations (HFOs) occur more frequently in the SOZ, [2][3][4][5][6][7][8][9] and the surgical removal of brain regions with high incidences of HFOs has been correlated to a higher likelihood of seizure freedom after surgery. 2,3,[10][11][12][13] These results suggest that HFOs may be a valuable marker for localization of epileptogenic tissue during surgical planning. Moreover, HFOs occur in interictal periods, so their use may enable clinicians to shorten the duration of invasive monitoring.…”
Section: Introductionmentioning
confidence: 81%
“…Several other studies have suggested that HFO amplitude differs between SOZ and nSOZ channels. One study has shown amplitude to be significantly higher in SOZ compared to non-SOZ electrodes (regardless of contact location) during interictal, preictal, and ictal periods, 11 but others have shown that this difference was not significant during nonictal periods. 44 Furthermore, pathological HFOs have been reported to demonstrate higher amplitude than physiologically-induced HFOs.…”
Section: Characteristics Of Ahfa and Chfomentioning
confidence: 99%